Disentangling drivers behind fungal diversity gradients along altitude and latitude - Barbi, Florian; Martinović, Tijana; Odriozola, Iñaki; Machac, Antonin; Moravcová, Andrea; Algora, Camelia; Ballian, Dalibor; Barthold, Sebastian; Brabcová, Vendula; Awokunle Hollá, Sandra; Human, Zander; Kraigher, Hojka; et al. (The New phytologist, 2025)
Gradients in species diversity across elevations and latitudes have fascinated biologists for decades. While these gradients have been well documented for macroorganisms, there is limited consensus about their universality, shape and drivers for microorganisms, such as fungi, despite the importance of fungal diversity for ecosystem functions and services. We conducted a comprehensive survey of fungal species richness in forests across 17 elevational transects along a latitudinal gradient covering the continental scale of Europe. Diversity patterns along elevational and latitudinal gradients differed among fungal ecological guilds. Diversity of saprotrophs declined with elevation while ectomycorrhizal (ECM) fungal diversity peaked in mid-elevations. Moreover, the diversity of root endophytic fungi increased with latitude but did not change with elevation. Bayesian species distribution modeling suggests that fungal diversity is structured by deterministic rather than stochastic drivers. Importantly, ECM fungal diversity pattern persists even after accounting for the effects of environmental conditions. These results suggest that environmental conditions differentially shape the diversity of fungal guilds along elevational and latitudinal gradients, but this goes beyond soil and climatic factors in the case of ECM fungi. This study paves the way toward a better understanding of fungal diversity gradients across elevations and latitudes, with possible implications for macroecological theory, conservation and management.
Keywords: Biodiversity; Mycorrhizae; join species distribution models; Fungi; nadmořská výška; zeměpis; Bayes Theorem; biogeography; saprotrophic fungi; Europe; biodiverzita; ectomycorrhizal fungi; houby; Geography; Evropa; fungal diversity; Altitude; altitudinal and latitudinal gradients; Bayesova věta; root endophytic fungi; mykorhiza; climate